2014
DOI: 10.3906/vet-1307-19
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effects of chitosan, plant oils, and different diets on rumen metabolism and protozoan population in sheep

Abstract: An efficient ecofriendly method for the alkylation reaction of various imines is described by a simple one-pot reaction of aldehydes, amines and alkyl iodides in the presence of AgI nanoparticles in aqueous media. Silver iodide nanoparticles mediated an enhanced rate and facility of reaction and showed high influence in the green synthesis of some amine derivatives. Moreover, this nanoparticle increased the yields of products and decreased the reaction times in all cases. The heterogeneous mediator was fully c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
26
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 40 publications
8
26
0
2
Order By: Relevance
“…Our results are in agreement with those of the authors cited above. The number of species in the genera Diplodinium and Ophryoscolex decreased before feeding and 8 h after feeding when sheep were fed rapeseed oil; this is consistent with the results of in vitro study by Wencelova et al (2014), who reported that the addition of rapeseed oil decreased the number of Enoploplastron triloricatum and Polyplastron multivesiculatum (subfamily Diplodininae) as well as Ophryoscolex c. tricronatus (subfamily Ophryoscolecinae). Rapeseed oil is rich in unsaturated acids, oleic acid C18:1, and linoleic acid C18:2, and a large amount of unsaturated fatty acids may reduce the ciliate population in the rumen.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our results are in agreement with those of the authors cited above. The number of species in the genera Diplodinium and Ophryoscolex decreased before feeding and 8 h after feeding when sheep were fed rapeseed oil; this is consistent with the results of in vitro study by Wencelova et al (2014), who reported that the addition of rapeseed oil decreased the number of Enoploplastron triloricatum and Polyplastron multivesiculatum (subfamily Diplodininae) as well as Ophryoscolex c. tricronatus (subfamily Ophryoscolecinae). Rapeseed oil is rich in unsaturated acids, oleic acid C18:1, and linoleic acid C18:2, and a large amount of unsaturated fatty acids may reduce the ciliate population in the rumen.…”
Section: Discussionsupporting
confidence: 80%
“…These results are consistent with findings of Cieslak et al (2015), who reported that the density of the ciliate population in the rumen of cows significantly decreased 3 and 6 h after feeding a diet containing a mixture of rapeseed and fish oils. Wencelova et al (2014) showed that the density of total protozoa as well as that of Entodinium spp. decreased when hay and barley grains (800 : 200 or 500 : 500 w/w) were incubated with rapeseed oil.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors can be related to micN production reduction including changes in ruminal fermentation and bacterial populations, and decreased feed intake and nutrient digestibility of cows fed WRS+CHI. In addition, evidence indicates that CHI can inhibit ciliate protozoal populations in a lower degree in comparison with vegetable oils (Wencelová et al, 2014). The inhibitory effects of lipids on protozoa can improve the efficiency of microbial protein synthesis even with a reduction of OM and NDF digestibility (Doreau and Ferlay, 1995;Eugène et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Whereby propionate and methane are competing substances for hydrogen reception, lipid addition can increase ruminal propionate concentration and decrease methane synthesis (Eugene et al (2004)). Likewise, Wencelova et al (2014) found that chitosan inhibits some protozoan populations, but with lower intensity than vegetables oils. In this study, however, chitosan had no effect on ruminal VFA profile and microbial protein synthesis, using purine derivatives as marker.…”
Section: Tablementioning
confidence: 99%